Transforming the IT services lifecycle with AI technologies. (2018) - Kloeckner, Kristof; Davis, John; Fuller, Nicholas C; Lanfranchi, Giovanni; Pappe, Stefan; Paradkar, Amit; Shwartz, Larisa; Surendra, Maheswaran; Wiesmann, Dorothea
No abstract available